Divergent effects of a Bacillus biofertilizer immobilized in guinea pig manure biochar: Boosting productivity vs. enhancing nutritional quality in maca monocultures - Richard Solórzano; Ana Carranza-Ramirez; Nora Vera-Obando; Rosario Javier-Astete; Alberto Arias-Arredondo; Melina Lopez-Rodriguez; Michell K. Arroyo-Julca; Excela Saavedra-Flores; Cinthia Quispe-Apaza; Lizbeth Mamani-Rojas; Juancarlos Cruz; Angel Montes Osorio; et al. (Applied Soil Ecology, 2026)

The Missing Global South in Climate Change Biology: Towards Equitable Knowledge Inclusion for Effective Global Solutions - Wesley Dáttilo; Rodrigo Beas‐Luna; Alma Mendoza‐Ponce; Angela Nava‐Bolanos; Angela P. Cuervo‐Robayo; Carolina Ureta; Constantino Gonzalez‐Salazar; Cuauhtemoc Saenz‐Romero; Daniel Jimenez‐Garcia; David A. Prieto‐Torres; Eduardo Cuevas; Gabriela Castano‐Meneses; et al. (Global Change Biology, 2026)
Over the last decades, climate change biology has become a central field in global science, yet knowledge production and its inclusion in global strategies remain profoundly unequal. Our bibliometric analysis of over 580,000 records shows that ~80% of author affiliations come from Global North institutions, meaning that research agendas, theoretical frameworks, and priorities are still largely shaped outside the regions with the highest biodiversity and greatest vulnerability to climate change. This imbalance reflects structural and historical inequalities that limit the ability of Global South countries to conduct autonomous research and sustain long‐term monitoring. When research and funding originate abroad, local scientists are often excluded, leading to the loss of traditional knowledge, regional perspectives, and long‐term capacity building. These dynamics leave tropical and subtropical bioregions (generally in the Global South) underrepresented in global climate knowledge. To address this imbalance, we propose six actions: invest in infrastructure and monitoring, strengthen local research networks, link funding to capacity building, promote open and equitable data access, connect science with regional policies, and foster intersectoral collaboration. We argue that truly effective climate change biology must be global, equitable, and diverse.

Decision-making in open carpooling programs: Perspectives of drivers versus passengers - Willis Simancas; Cristian Vinasco; Daniel Rosas-Satizábal; Hernan Alberto Ortiz-Ramirez; Alvaro Rodriguez-Valencia (Travel Behaviour and Society, 2024)

Variable response of Red Sea coral communities to recent disturbance events along a latitudinal gradient - Nicholas M. Hammerman; Alberto Rodriguez-Ramirez; Timothy L. Staples; Thomas M. DeCarlo; Vincent Saderne; George Roff; Nicole Leonard; Jian-xin Zhao; Susann Rossbach; Michelle N. Havlik; Carlos M. Duarte; John M. Pandolfi (Marine Biology, 2021)

Fine-scale time series surveys reveal new insights into spatio-temporal trends in coral cover (2002–2018), of a coral reef on the Southern Great Barrier Reef - Chris Roelfsema; Eva M. Kovacs; Julie Vercelloni; Kathryn Markey; Alberto Rodriguez-Ramirez; Sebastian Lopez-Marcano; Manuel Gonzalez-Rivero; Ove Hoegh-Guldberg; Stuart R. Phinn (Coral Reefs, 2021)

Regional wind pattern, a basis for defining the appropriate lapse of time for sugarcane burning in the Cauca Valley (Colombia) - Mónica Preciado Vargas; Héctor Alberto Chica Ramirez; Efraín Solarte Rodriguez; Javier Alí Carbonell Gonzalez; Andrés Javier Peña Quiñones (Environment, Development and Sustainability, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Coral Reef Community Changes in Karimunjawa National Park, Indonesia: Assessing the Efficacy of Management in the Face of Local and Global Stressors - Emma V Kennedy; Julie Vercelloni; Benjamin P Neal; Ambariyanto; Dominic E.P. Bryant; Anjani Ganase; Patrick Gartrell; Kristen Brown; Catherine J.S. Kim; Mu’alimah Hudatwi; Abdul Hadi; Agus Prabowo; et al. (Journal of Marine Science and Engineering, 2020)
Karimunjawa National Park is one of Indonesia’s oldest established marine parks. Coral reefs across the park are being impacted by fishing, tourism and declining water quality (local stressors), as well as climate change (global pressures). In this study, we apply a multivariate statistical model to detailed benthic ecological datasets collected across Karimunjawa’s coral reefs, to explore drivers of community change at the park level. Eighteen sites were surveyed in 2014 and 2018, before and after the 2016 global mass coral bleaching event. Analyses revealed that average coral cover declined slightly from 29.2 ± 0.12% (Standard Deviation, SD) to 26.3 ± 0.10% SD, with bleaching driving declines in most corals. Management zone was unrelated to coral decline, but shifts from massive morphologies toward more complex foliose and branching corals were apparent across all zones, reflecting a park-wide reduction in damaging fishing practises. A doubling of sponges and associated declines in massive corals could not be related to bleaching, suggesting another driver, likely declining water quality associated with tourism and mariculture. Further investigation of this potentially emerging threat is needed. Monitoring and management of water quality across Karimunjawa may be critical to improving resilience of reef communities to future coral bleaching.

Climate Change and Atlantic Multidecadal Oscillation as Drivers of Recent Declines in Coral Growth Rates in the Southwestern Caribbean - Luis D. Lizcano-Sandoval; Ángela Marulanda-Gómez; Mateo López-Victoria; Alberto Rodriguez-Ramirez (Frontiers in Marine Science, 2019)